Solvent‐Engineered Scalable Production of Polysulfide‐Blocking Shields to Enhance Practical Lithium–Sulfur Batteries. Issue 8 (17th May 2018) - Qin, Jin‐Lei; Peng, Hong‐Jie; Huang, Jia‐Qi; Zhang, Xue‐Qiang; Kong, Long; Xie, Jin; Zhao, Meng; Liu, Ruiping; Zhao, Huiyou; Zhang, Qiang
Abstract: Lithium–sulfur (Li–S) batteries are very promising next‐generation energy‐storage devices due to the extremely high energy density. However, the low capacity and poor cycling life induced by the shuttle effect of polysulfide intermediates impede the practical application of Li–S batteries. Here, a very effective solvent‐engineering strategy is proposed to fabricate thin, compact, and multifunctional binary solvent–engineered polysulfide‐blocking shields (BBSs) with a superior capability of retarding the shuttle and stabilizing the cathode/anode. The Li–S batteries with a BBS separator exhibit enhanced cell kinetics, superb cycling stability with a low decay rate of 0.078% per cycle for 400 cycles at 0.5 C, and a high areal capacity of 4.91 mAh cm −2 after 100 cycles at 2.37 mA cm −2 . In addition, the industrially viable fabrication of BBS is readily employed in practical Li–S pouch cells. The concept of solvent engineering not only renders functional interlayers/separators that significantly improve the Li–S battery performance but also is simple, versatile, and scalable to be adopted for many other promising research fields of energy storage and materials chemistry. Abstract : A solvent‐engineering strategy is proposed to achieve thin, compact, and multifunctional binary solvent–engineered polysulfide‐blocking shields with a superior capability for retarding the shuttle and stabilizing electrodes. This such concept renders functional interlayers/separators for enhanced Li–S batteries and is simple, versatile, and scalable for adoption in other research fields of energy storage materials.